Kejahatan Konspirasi dan Perbantuan dalam Terorisme - Ambarita, Folman P.; Idharudin, Taufiq (Al-Ishlah: Jurnal Ilmiah Hukum, 2023)
This study aims to understand the application of material criminal law to the crime of conspiracy and assistance to commit terrorism. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that the definition of criminal conspiracy in Article 88 of the Penal Code encompasses an agreement between two or more individuals to commit a crime. Initial discussions not directly related to crime planning do not fall within the category of a malicious conspiracy. Furthermore, concerning the crime of terrorism, material criminal law does not differentiate between the roles of conspirators, assistants, and main perpetrators in terrorism. Consequently, an agreement to commit a terrorist crime made by two or more individuals already fulfils the element of criminal conspiracy. In this context, conspirators and terrorism assistants can be prosecuted according to Government Regulation in Lieu of Law Number 1 of 2002, even if the planned terrorist act has not been executed. Therefore, it is recommended for law enforcers, including POLRI, Prosecutors, and Judges, to pay close attention to the nuances of the criminal conspiracy definition according to the Penal Code and Government Regulation in Lieu of Law Number 1 of 2002 in the eradication of criminal acts of terrorism. It is crucial to distinguish between initial discussions that do not indicate preparation for a criminal act and explicit agreements to commit a terrorist crime. Law enforcers must apply a thorough understanding of how material criminal law classifies conspirators, assistants, and main perpetrators without distinction in terrorism cases. Thus, fair and accurate handling of individuals planning terrorist crimes can be realized while upholding the principles of justice and proportionality in law enforcement.